Ex vivo Generation of Platelets from Umbilical Cord Blood Hematopoietic Stem Cells with Amniotic Membrane Mesenchymal Stem Cells Support - Mardiah Suci Hardianti (Faculty of Medicine Universitas Gadjah Mada, 2013)
ABSTRACTBackground: Platelet refractoriness is a major problem among patients requiring repeated transfusion. Production of less immunogenic platelets is required to overcome this problem. Umbilical cord blood (UCB) is rich in hematopoietic stem cells (HSC), which may serve as a potential source of less immunogenic ex vivo generated platelet. Development of methods to generate platelet from HSC in UCB with additions of various growth factors made a very high production cost. Amniotic membrane is widely known as the best source of mesenchymal stem cells (MSC), which may support the growth of platelet from HSC in UCB due to its abundant productions of cytokines and low cost . Aim: This study aimed to generate platelet from UCB co-cultured with MSC derived from amniotic membrane.Methods: Gradient density separation was performed to obtain mononuclear cells from UCB. The resulted mononuclear (MN) cells were selected for CD34+ by magnetic sorter beads. CD34+ HSC and non-CD34+ MN cells were each cultured in standard medium plus 10 ng/ml thrombopoietin (TPO), 50 ng/ml stem cell factor (SCF), and 25 ng/ml interleukin-11 (IL-11), with or without co-cultured with MSC. The MSC was also cultured alone with the addition of the above mentioned cytokines. Cultures were incubated in 37o C with 5% CO2 and half of the medium was changed twice a week. Formations of platelets were confirmed by flowcytometry after two weeks culturing.Results: Total number of CD34+ HSC was 1x106, the non-CD34+ MNC was 1.78x107 and the MSC was 3x105. Following the culture systems, the number of platelets produced from CD34+ HSC with and without MSC were 1.17% and 0.84%, respectively. The numbers of platelets produced from non-CD34+ MN cells with and without MSC were 7.94% and 8.85%, respectively. The number of platelets produced from 105 MSC was 1.43%.Conclusions: There was a greater increment in ex vivo production of platelets in CD34+ HSC isolated from UCB co-cultured with MSC, compared to that of without MSC. Further study to evaluate the significancy of the increament and the platelet function produced by this system is warranted. Keywords: platelet, hematopoietic stem cells, - mesenchymal stem cells